The Effectiveness of Chlorella sp. in Decreasing Nitrate and PhosphateConcentration in The Bioflock System Intensive Aquaculture Waste - Geliska Wahyuni; Eko Purwanto; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTIn the bioflock system intensive aquaculture, the waste was removed everyday. The waste contain high concentration of nitrate and phosphate. Effort in reducing those organic matters can be done by usingChlorella sp. A study aims to determine the effectiveness of Chlorella sp. in decreasing nitrate and phosphate concentration in thewaste was conducted in August 2019. There was a CRD method with 4 treatments, namely the addition of 0 sel/ml (control); 333sel/ml (P1); 3.330sel/ml (P2); 33.300sel/ml (P3) and 333.000sel/ml (P4) of Chlorella sp. in 4 liters of wate water. Nitrate and phosphate concentration in the water were checked in the 1st, 4th and 7th days. Results shown that the highest nitrate increased was in the P1 at the 7th day (138%), while that of the phosphate lost was in the P4 at the 7th day (98%). Based on data obtained, it can be concluded that Chlorellasp. was not able todecreasenitrate concentration,while of the phosphate was able to decrease in the waste water originated from biofloc system intensive aquacultre. Keywords:Nitrate, phosphate, Chlorellasp.bioflock, aquaculture waste.